Is it worth screening elective orthopaedic patients for carriage of Staphylococcus aureus? A part-retrospective case–control study in a Scottish hospital. Issue 9 (6th September 2016) - Dancer, Stephanie J; Christison, Fraser; Eslami, Attaolah; Gregori, Alberto; Miller, Roslyn; Perisamy, Kumar; Robertson, Chris; Graves, Nick
Abstract : Background: With recent focus on methicillin-resistant Staphylococcus aureus (MRSA) screening, methicillin-susceptible S. aureus (MSSA) has been overlooked. MSSA infections are costly and debilitating in orthopaedic surgery. Methods: We broadened MRSA screening to include MSSA for elective orthopaedic patients. Preoperative decolonisation was offered if appropriate. Elective and trauma patients were audited for staphylococcal infection during 2 6-month periods (A: January to June 2013 MRSA screening; B: January to June 2014 MRSA and MSSA screening). Trauma patients are not screened presurgery and provided a control. MSSA screening costs of a modelled cohort of 500 elective patients were offset by changes in number and costs of MSSA infections to demonstrate the change in total health service costs. Findings: Trauma patients showed similar infection rates during both periods (p=1). In period A, 4 (1.72%) and 15 (6.47%) of 232 elective patients suffered superficial and deep MSSA infections, respectively, with 6 superficial (2%) and 1 deep (0.3%) infection among 307 elective patients during period B. For any MSSA infection, risk ratios were 0.95 (95% CI 0.41 to 2.23) for trauma and 0.28 (95% CI 0.12 to 0.65) for elective patients (period B vs period A). For deep MSSA infections, risk ratios were 0.58 (95% CI 0.20 to 1.67) for trauma and 0.05 (95% CI 0.01 to 0.36) for elective patients (p=0.011). There were 29.12 fewer deep infections in the modelled cohort of 500 patients, with a cost reduction of £831 678 for 500 patients screened. Conclusions: MSSA screening for elective orthopaedic patients may reduce the risk of deep postoperative MSSA infection with associated cost-benefits.